Various forms of injury caused by judo - Sasa, T. (Association for the Scientific Studies on Judo, Kodokan, 1958)
At the 9th Meeting of the Orthopedie Society, Prof. K. Saito reported on the statistical observations made on approximately 4000 cases of trauma sustained during the performance of various sports. The present paper is a study of the various forms of injury sustained by high grade holders during their long course of training in judo.